Editorial: Thematic series on software engineering from a social network perspective. Issue 1 (August 2015) - Gerosa, Marco; Redmiles, David; Bjørn, Pernille; Sarma, Anita
Abstract In the Internet age, the concept of social network is emerging as both a useful means for understanding software development activities and a concept for designing software tools to support these activities. Employing Social Networking is useful in part, because it brings a focus to stakeholders in software development including developers, their managers, their support staff, QA analysts, requirement engineers, etc. Social networks represent how people communicate, coordinate, cooperate, and develop working relationships. The concept is also useful as it reflects the network-centric organization for dealing with highly inter-dependent artifacts–including complex source code, systems and subsystems, requirement and specification documents, etc. However, the knowledge on social network in software engineering is spread across the literature and the term social network is used for multiple purposes, such as social networking sites, social capital, interpersonal connections, and social structures. This thematic series puts together papers that employ the concept of social networks either in studying software development from an empirical approach or use the concept as a central basis for developing software tool support. Readers will find in this issue a centralized resource for research in this area.